2015
DOI: 10.1016/j.cub.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Inhibition of the FGFR1c Isoform Induces a Catabolic Lean State in Siberian Hamsters

Abstract: Hypothalamic tanycytes are considered to function as sensors of peripheral metabolism. To facilitate this role, they express a wide range of receptors, including fibroblast growth factor receptor 1 (FGFR1). Using a monoclonal antibody (IMC-H7) that selectively antagonizes the FGFR1c isoform, we investigated possible actions of FGFR1c in a natural animal model of adiposity, the Siberian hamster. Infusion of IMC-H7 into the third ventricle suppressed appetite and increased energy expenditure. Likewise, periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…It was previously shown that antibody-mediated targeting of the FGFR1c receptor reduced body weight, adiposity, and insulin resistance in animal models of obesity and type II diabetes (2729). Subsequent in situ hybridization studies in the Siberian hamster revealed a high level expression of the FGFR1c in tanycytes, consistent with previous qPCR studies in the mouse (30, 31). Targeting of the FGFR1c in the long day (LD) obese Siberian hamster peripherally and centrally via intracerebroventicular infusion of a monoclonal FGFR1c antibody reduced food intake and body weight, which was associated with a decrease in expression of DIO2 in the ependymal cell layer containing tanycytes (31).…”
Section: Hypothalamic Tanycytes As Mediators Of Energy Homeostasissupporting
confidence: 87%
See 1 more Smart Citation
“…It was previously shown that antibody-mediated targeting of the FGFR1c receptor reduced body weight, adiposity, and insulin resistance in animal models of obesity and type II diabetes (2729). Subsequent in situ hybridization studies in the Siberian hamster revealed a high level expression of the FGFR1c in tanycytes, consistent with previous qPCR studies in the mouse (30, 31). Targeting of the FGFR1c in the long day (LD) obese Siberian hamster peripherally and centrally via intracerebroventicular infusion of a monoclonal FGFR1c antibody reduced food intake and body weight, which was associated with a decrease in expression of DIO2 in the ependymal cell layer containing tanycytes (31).…”
Section: Hypothalamic Tanycytes As Mediators Of Energy Homeostasissupporting
confidence: 87%
“…Subsequent in situ hybridization studies in the Siberian hamster revealed a high level expression of the FGFR1c in tanycytes, consistent with previous qPCR studies in the mouse (30, 31). Targeting of the FGFR1c in the long day (LD) obese Siberian hamster peripherally and centrally via intracerebroventicular infusion of a monoclonal FGFR1c antibody reduced food intake and body weight, which was associated with a decrease in expression of DIO2 in the ependymal cell layer containing tanycytes (31). This further supports the hypothesis that tanycytes are an important component of the mechanism by which the hypothalamus integrates central and peripheral signals to regulate energy homeostasis.…”
Section: Hypothalamic Tanycytes As Mediators Of Energy Homeostasissupporting
confidence: 87%
“…However, key downstream phosphorylation events are lost in the aged cohort in response to treatment. Previously we demonstrated that the actions of FGF21 mimetics were diminished in SD animals 21, 22 . However, results were equivocal as to whether this was a consequence of the central photoperiodic state or a result of reduced adiposity.…”
Section: Discussionmentioning
confidence: 90%
“…A monoclonal antibody targeting the hypothalamic FGFR1 causes potent hypophagia in rodents and non-human primates 22, 29 . The reduced food intake demonstrated in these studies is associated with reduced meal duration and frequency in young animals, suggesting a possible effect on satiety and/or reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation